Leituras acadêmicas na graduação: ressonâncias na pós-graduação en Brasil - Cláudio Rodrigues Da Silva (Ediciones Universidad de Salamanca, 2022)
We report results based on studies involving Higher Education professors, aiming to present aspects of their standings on the question of readings of basic bibliographies of Courses by graduation students. We emphasize, in this article, notes of professors who establish relations between Graduation and Post-Graduation in relation to readings. This is an exploratory study, based on bibliographical and empirical data, surveyed especially through semi-structured interviews. The participators present diverse standings on this topic, perceived as one the key components and also one of the main challenges of academic-scientific formation nowadays. The readings are characterized as a controversial and urgent theme, because of its relations with the quality of both Graduation and Post-Graduation.